Effect of post length on the fatigue resistance of bovine teeth restored with bonded fiber posts: A pilot study - Scotti, Roberto; Valandro, Luiz Felipe; Galhano, Graziela Avila Prado [UNESP]; Baldissara, Paolo; Bottino, Marco Antonio [UNESP] (My University, 2006)
This study evaluated the influence of the cementation length of glass fiber-reinforced composite (FRC) on the fatigue resistance of bovine teeth restored with an adhesively cemented FRC. Thirty roots of single-rooted bovine teeth were allocated to 3 groups (n = 10), according to the ratio of crown length/root length (post cementation length): group 1 = 2/3, group 2 = 1/2, and group 3 = 1/1. The roots were prepared, the fiber posts (FRC Postec Plus) were cemented, and the specimens were submitted to 2 million mechanical cycles. After fatigue testing, a score was given based on the number of fatigue cycles until fracture, and data were submitted to statistical analysis. All specimens were resistant to fatigue. Taking into account the methodology and results of this study, the evaluated fiber posts can be cemented based on the ratio of crown/root at 1/1. Further clinical studies must be conducted to verify this ratio.